2020
DOI: 10.1093/humrep/deaa217
|View full text |Cite
|
Sign up to set email alerts
|

Decidua-derived granulocyte macrophage colony-stimulating factor induces polymorphonuclear myeloid-derived suppressor cells from circulating CD15+ neutrophils

Abstract: STUDY QUESTION Do decidua-derived factors stimulate the conversion of circulating neutrophils to polymorphonuclear myeloid-derived suppressor cells (PMN-MDSCs) in early human pregnancy? SUMMARY ANSWER Circulating neutrophils can acquire PMN-MDSC-like phenotypes and function via phosphorylated signal transducer and activator of transcription 5/programmed death ligand 2 (pSTAT5/PD-L2) signalling after stimulation with decidua-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 70 publications
1
16
1
Order By: Relevance
“…In early pregnancy, it is believed that circulating neutrophils can acquire a MDSC phenotype upon migration to the maternal–fetal interface following stimulation with decidua‐derived GM‐CSF. Stimulation of CD15 + neutrophils with GM‐CSF activates STAT5 signalling, leading to the induction PD‐L2 expression which consequently is used by the neutrophil to restrain T‐cell proliferation though PD‐1 signalling [ 97 ]. CXCR2 has also been implicated with the recruitment of G‐MDSCs in decidual tissue and induces arginase I, an effector molecule used by MDSCs to regulate T‐cell activity [ 98 ].…”
Section: The Cross‐talk Between Neutrophils and T Cellsmentioning
confidence: 99%
“…In early pregnancy, it is believed that circulating neutrophils can acquire a MDSC phenotype upon migration to the maternal–fetal interface following stimulation with decidua‐derived GM‐CSF. Stimulation of CD15 + neutrophils with GM‐CSF activates STAT5 signalling, leading to the induction PD‐L2 expression which consequently is used by the neutrophil to restrain T‐cell proliferation though PD‐1 signalling [ 97 ]. CXCR2 has also been implicated with the recruitment of G‐MDSCs in decidual tissue and induces arginase I, an effector molecule used by MDSCs to regulate T‐cell activity [ 98 ].…”
Section: The Cross‐talk Between Neutrophils and T Cellsmentioning
confidence: 99%
“…Recent studies have indicated that G-CSF pretreatment attenuates acute ischemia-reperfusion injury and subsequent renal fibrosis by increasing MDSC infiltration into the kidney (12). GM-CSF also stimulates neutrophils to MDSCs conversion in early human pregnancy (14). Since there is also an evidence that bone marrow (BM)-induced MDSCs exhibit more potent suppressive function than mice-isolated MDSCs (13), here raises new questions: is there a difference in the function of MDSCs induced in vitro or in vivo?…”
Section: Introductionmentioning
confidence: 99%
“… 72 Compared to peripheral blood, elevated PD‐L1 expression by CD4 + T, Treg, NKT‐like and CD56 + NK cells were also found with the increased PD‐1 expression by decidual CD8 + T, CD4 + T and NKT‐like cells. 77 PD‐L2 is expressed on the decidual polymorphonuclear myeloid‐derived suppressor cells (PMN‐MDSCs) and neutrophils 76 , 80 and is also expressed in syncytiotrophoblasts. 81 T‐cell proliferation is suppressed by both decidual PMN‐MDSCs and decidual explant supernatant (DES)‐conditioned neutrophils via PD‐1 signalling.…”
Section: Immune Checkpoint Moleculesmentioning
confidence: 99%
“…A shift from circulating neutrophils to PMN‐MDSC‐like phenotypes requires stimulation with decidua‐derived granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) by pSTAT5/PD‐L2 signaling. 80 Overall, the PD‐1‐PD‐L1 axis not only regulates T cells including promoting a shift to Type 2 helper T‐cell (Th2) bias 82 and Treg cell proliferation, 83 , 84 as well as reducing CD8 + T accompanied by NKG2D activating receptor, 77 , 85 , 86 , 87 , 88 , 89 , 90 Th17 83 , 91 and TFH 92 , 93 responses but also plays an important role in innate immune cells for pregnancy maintenance. 94 …”
Section: Immune Checkpoint Moleculesmentioning
confidence: 99%